2020
DOI: 10.1155/2020/8812797
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Novel Insecticide Flupyradifurone and Its Two Metabolites in Traditional Chinese Herbal Medicines Using Modified QuEChERS and High-Performance Liquid Chromatography-Tandem Mass Spectrometry

Abstract: In this study, an analytical method for the simultaneous determination of the novel insecticide flupyradifurone and its two metabolites in a variety of traditional Chinese herbal medicines was developed for the first time using high-performance liquid chromatography-tandem mass spectrometry. A simple and efficient method using dispersive solid-phase extraction was employed for the pretreatment of the samples. Several extractions and cleanup strategies were evaluated. The recoveries (n = 15) of flupyradifurone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…It was reported that 6-CNA and DFA were difficult to extract in water using the QuEChERS method [ 13 ] because of their octanol–water partition coefficients (Log P of the 6-CNA and DFA was 0.98 and −0.11, respectively) [ 10 ]. We also found that the extraction efficiencies of DFA and 6-CNA improved significantly upon the addition of formic acid, and the recoveries did not increase when the concentration of formic acid reached 2%.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that 6-CNA and DFA were difficult to extract in water using the QuEChERS method [ 13 ] because of their octanol–water partition coefficients (Log P of the 6-CNA and DFA was 0.98 and −0.11, respectively) [ 10 ]. We also found that the extraction efficiencies of DFA and 6-CNA improved significantly upon the addition of formic acid, and the recoveries did not increase when the concentration of formic acid reached 2%.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the sample clean-up process involved three typical clean-up agents, C18, PSA, and GCB. Notably, C18 can remove nonpolar and medium-polar compounds from polar samples; PSA mainly removes organic acids, pigments, sugars, and fats in nonpolar samples; and GCB is a weakly polar or nonpolar adsorbent that can remove impurities such as hydrophobic compounds like chlorophyll and carotenoids [23,26].…”
Section: Optimization Of Extraction and Purification Conditionsmentioning
confidence: 99%
“…monitored for food safety. Currently, studies on FPD in China have been limited to the establishment of analytical methods in traditional Chinese herbal medicines, fruits, vegetables, and nuts (Fang et al, 2020;Li et al, 2016Li et al, , 2018Mahdavi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The silverleaf whitefly ( Bemisia tabaci ) is a major pest during the growth stage of pepper, which can significantly reduce its yield (Buddidathi et al, 2016; Yang et al, 2010). Flupyradifurone (FPD, Figure 1) is a novel butenolide insecticide produced by Bayer Crop Science, which has a substantial effect on B. tabaci in pepper (Fang et al, 2020; Nauen et al, 2015). Currently in China, 17% flupyradifurone soluble concentrate (SL) is being registered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation